Scenes of Vienna - Reschka (engraver):::Creator:::::::::::: (Italy; Kunst-Anst. d. östr. Lloyd; Trieste)
Eleven scenes of Vienna and its environs from the mid-nineteenth century, including (counterclockwise from top left): Laxenburg, Schönbrunn, entrance to the Prater, Nussdorf, Greifenstein, Mödling, steamboat port in Nussdorf; Baden, Haus zu den Drei Raben in Brühl, meadow near Baden, panoramic view of Vienna from about the city.